Dispersing agent as well as preparation method and application thereof

By using dispersants of non-ionic polymers, organic carboxylic acids and polyhydroxyaldehydes in electrode slurry, the problem of insufficient solid content and fluidity of electrode slurry is solved, the performance and stability of lithium-ion batteries are improved, and the performance and stability of lithium-ion batteries are extended. The battery cycle life.

CN119315034APending Publication Date: 2025-01-14SHENZHEN DYNANONIC INNOVAZONE NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411398074.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing electrode dispersants cannot effectively improve the solid content and fluidity of the electrode slurry, resulting in limited performance of lithium-ion batteries.

Method used

Using a dispersant, including nonionic polymers, organic carboxylic acids and polyhydroxyaldehydes, the viscosity and solid content of the slurry are adjusted through complex adsorption, and interact with the surface functional groups of the electrode active material to reduce the surface of the solid-liquid interface. Tension improves the fluidity and stability of the electrode slurry.

Benefits of technology

It significantly improves the solid content and fluidity of the electrode slurry, prevents excessive dispersion and damage to the surface cladding of the electrode active material, improves the uniformity and electrochemical performance of the electrode sheet, and extends the cycle life of the lithium-ion battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315034A_ABST
    Figure CN119315034A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly relates to a dispersing agent and a preparation method and application thereof. The dispersing agent comprises the following raw material components in parts by mass: 25-50 parts of a nonionic polymer, 25-60 parts of organic carboxylic acid and 5-20 parts of polyhydroxy aldehyde. Components in the dispersant have surface functional groups which are the same as or similar to the electrode active material, so that a coating layer on the surface of the electrode active material can be prevented from being damaged due to excessive reaction. Moreover, components contained in the dispersing agent and synergism of the components play a great role in improving the dispersibility of the electrode slurry and reducing the viscosity of the slurry. Meanwhile, the effects of improving the solid content of the electrode slurry, improving the fluidity of the electrode slurry and preventing a coating layer on the surface of an electrode active material from being damaged due to excessive dispersion can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of battery technology, and in particular relates to a dispersant and a preparation method and application thereof. Background Art

[0002] The positive electrode sheet of a lithium-ion battery often includes components such as positive electrode materials, conductive glue, and binders. The positive electrode sheet is formed by first coating the prepared positive electrode slurry on a foil current collector, and then forming the positive electrode sheet after processes such as baking and rolling. The dispersion, viscosity, and other states of the positive electrode slurry will directly affect the coating quality of the positive electrode sheet, thereby affecting the performance of the lithium-ion battery. The solid content of the electrode slurry is closely related to the gram capacity of the battery. Increasing the solid content of the slurry can effectively increase the capacity of the battery. At present, in order to increase the capacity of lithium-ion batteries, the proportion of electrode active substances in the electrode slurry is usually increased. This will result in an excessively high solid content of the electrode slurry, which will make the electrode slurry viscous and poorly fluid, thereby affecting the coating effect of the electrode slurry, and further affecting the efficiency of the electrode sheet and lithium-ion battery preparation process.

[0003] Generally speaking, adding dispersants to electrode slurries is the main solution to improve the dispersion performance of slurries, reduce particle agglomeration, and improve slurry fluidity. However, although the dispersants currently available on the market can solve the dispersion problem of electrode slurries to a certain extent, there is still a need for better solutions to increase the solid content of electrode slurries and improve slurry fluidity. Summary of the invention

[0004] The purpose of the present application is to provide a dispersant and a preparation method and application thereof, aiming to solve the problem that the existing electrode dispersants are not effective in improving the solid content and fluidity of the electrode slurry to a certain extent.

[0005] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0006] In a first aspect, the present application provides a dispersant, comprising the following raw material components in parts by weight:

[0007] 25-50 parts of nonionic polymer, 25-60 parts of organic carboxylic acid, 5-20 parts of polyhydroxy aldehyde.

[0008] In some possible implementations, the organic carboxylic acid includes polyhydroxy carboxylic acid and long-chain carboxylic acid.

[0009] In some possible implementations, in the dispersant, the mass fraction of the polyhydroxy carboxylic acid is 20 to 40 parts, and the mass fraction of the long-chain carboxylic acid is 5 to 20 parts.

[0010] In some possible implementations, the polyhydroxy aldehyde has at least 2 hydroxyl groups.

[0011] In some possible implementations, the polyhydroxycarboxylic acid has at least 2 hydroxyl groups.

[0012] In some possible implementations, the number of carbon atoms in the carbon chain of the long-chain carboxylic acid is not less than 12.

[0013] In some possible implementations, the nonionic polymer contains at least one functional group selected from the group consisting of a hydroxyl group, a lactam group, and an amine group.

[0014] In some possible implementations, the weight average molecular weight of the non-ionic polymer is 10,000 to 50,000.

[0015] In some possible implementations, the weight average molecular weight of the long-chain carboxylic acid is 200-300.

[0016] In some possible implementations, the weight average molecular weight of the polyhydroxycarboxylic acid is 150-1800.

[0017] In some possible implementations, the weight average molecular weight of the polyhydroxy aldehyde is 180-360.

[0018] In some possible implementations, the non-ionic polymer includes at least one of methyl pyrrolidone, polyethylene glycol, polyvinyl alcohol, and polyacrylamide.

[0019] In some possible implementations, the polyhydroxycarboxylic acid includes at least one of citric acid, tartaric acid, phytic acid, and gallic acid.

[0020] In some possible implementations, the long-chain carboxylic acid includes at least one of palmitic acid, stearic acid, and fatty acid.

[0021] In some possible implementations, the polyhydroxy aldehyde includes at least one of glucose, fructose, and glyceraldehyde.

[0022] In some possible implementations, the dispersant further includes at least one solvent selected from N-methylpyrrolidone and N,N-dimethylformamide.

[0023] In some possible implementations, the dispersant further includes a solvent in an amount of 70% to 95% by mass.

[0024] In a second aspect, the present application provides a method for preparing a dispersant, comprising the following steps:

[0025] 25-50 parts of nonionic polymer, 25-60 parts of organic carboxylic acid, 5-20 parts of polyhydroxy aldehyde and solvent are mixed to prepare a dispersant.

[0026] In some possible implementations, the organic carboxylic acid includes 20 to 40 parts of polyhydroxy carboxylic acid and 5 to 20 parts of long-chain carboxylic acid.

[0027] In some possible implementations, the mass percentage of the solvent in the dispersant is 70% to 95%.

[0028] In some possible implementations, the non-ionic polymer includes at least one of methyl pyrrolidone, polyethylene glycol, polyvinyl alcohol, and polyacrylamide.

[0029] In some possible implementations, the organic carboxylic acid includes at least one polyhydroxy carboxylic acid selected from the group consisting of citric acid, tartaric acid, phytic acid, and gallic acid.

[0030] In some possible implementations, the organic carboxylic acid includes at least one long-chain carboxylic acid selected from palmitic acid, stearic acid, and fatty acids.

[0031] In some possible implementations, the polyhydroxy aldehyde includes at least one of glucose, fructose, and glyceraldehyde.

[0032] In some possible implementations, the solvent includes at least one of N-methylpyrrolidone and N,N-dimethylformamide.

[0033] In a third aspect, the present application provides a secondary battery, comprising an electrode sheet and an electrolyte; wherein the electrode slurry for preparing the electrode sheet comprises an electrode active material, a conductive agent, a binder, a solvent and the above-mentioned dispersant and / or the dispersant prepared by the above-mentioned method.

[0034] In some possible implementations, in the electrode slurry, the mass percentage of the dispersant is 0.1% to 0.5%.

[0035] In some possible implementations, the electrode sheet is a positive electrode sheet, and the surface of the electrode active material has a carbon coating layer grafted with at least one group of carbonyl, ether, and phenolic hydroxyl.

[0036] The dispersant provided in the first aspect of the present application has a certain complex adsorption effect between the functional groups of each component. Among them, the non-ionic polymer has no charged group and is non-ionic, and can better adjust the viscosity of the slurry in the dispersant. On the one hand, the terminal carboxyl group of the organic carboxylic acid can undergo complex adsorption with non-ionic polymers such as hydroxyl, lactam, amine, etc., forming an effective steric hindrance. On the other hand, the organic carboxylic acid can interact with some unique functional groups on the surface of the electrode active material to effectively reduce the surface tension of the solid-liquid interface. The functional groups on the polyhydroxy aldehyde are similar to those on the surface of the electrode active material, which play an electrostatic repulsion role and play a synergistic dispersion role with the organic carboxylic acid. Therefore, the dispersant formula can effectively promote the decrease of slurry viscosity, inhibit slurry gelation, increase the solid content of battery pole pieces, and thus improve battery performance. Among them, if the content of the non-ionic polymer is too low, it is not conducive to providing sufficient steric hindrance, and if the content is too high, the slurry viscosity will rise due to its huge molecular weight. If the content of organic carboxylic acid is too low, the anchoring effect with the surface of the electrode active material is weak, which is not conducive to viscosity reduction. If the content is too high, it may cause instability of the electrode slurry and stratification. If the content of polyhydroxy aldehyde is too high, it is not conducive to reducing the viscosity of the electrode slurry. If the content is too low, it is not enough to provide functional groups similar to those of the electrode active material.

[0037] The preparation method of the dispersant of the second aspect of the present application is to fully dissolve and disperse 25 to 50 parts of non-ionic polymer, 25 to 60 parts of organic carboxylic acid, and 5 to 20 parts of polyhydroxy aldehyde in a solvent, and observe that the solution is in a clear state to obtain a dispersant. The preparation process is simple and suitable for industrial large-scale production and application. There is a certain complexation adsorption effect between the functional groups of the components in the prepared dispersant. Among them, the non-ionic polymer has no charged group and is non-ionic, and can better adjust the viscosity of the slurry in the dispersant. The amount of non-ionic polymer fully ensures that it forms an effective steric hindrance with organic carboxylic acid through complexation adsorption, thereby increasing the solid content of the slurry. The amount of organic carboxylic acid and polyhydroxy aldehyde not only ensures that the slurry has a suitable viscosity, but also can effectively improve the dispersion stability, fluidity and other characteristics of the slurry; and the functional groups in organic carboxylic acid and polyhydroxy aldehyde are similar to the groups on the surface of the electrode active material in the electrode slurry, which is beneficial to prevent the coating layer on the surface of the electrode active material from being destroyed by excessive reaction. Through the joint action of various components in the dispersant, the solid content of the electrode slurry can be increased, the fluidity of the electrode slurry can be improved, and excessive dispersion can be prevented from destroying the surface coating layer of the electrode active material.

[0038] In the third aspect of the present application, the electrode slurry for preparing the electrode sheet is added with the above-mentioned dispersant, which can simultaneously increase the solid content of the electrode slurry, improve the fluidity of the electrode slurry, and prevent excessive dispersion from damaging the surface coating of the electrode active material through the joint action of various components. Therefore, it is beneficial to improve the uniformity, stability, content of electrode active materials and other properties of the electrode sheet, thereby improving the electrochemical properties of the secondary battery such as gram capacity, stability, and cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0040] Figure 1 Schematic diagram of the process for preparing the dispersant provided in the embodiment of the present application;

[0041] Figure 2 It is a real shot of the discharge flow of the positive electrode slurry provided in the verification examples B1 and B4 and the verification comparative examples B1 and B8 of this application;

[0042] Figure 3 It is a charge and discharge curve diagram of the battery provided in Verification Example B1 of this application;

[0043] Figure 4 It is a charge and discharge curve diagram of the battery provided in Verification Example B4 of this application;

[0044] Figure 5 It is a charge and discharge curve diagram of the battery provided by comparative example B1 of the present application;

[0045] Figure 6 It is a charge and discharge curve diagram of the battery provided in comparative example B8 for verification of the present application. DETAILED DESCRIPTION

[0046] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0047] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0048] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0049] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0050] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0051] The weight of the relevant components mentioned in the embodiments of the present specification can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components in the embodiments of the present specification is proportionally enlarged or reduced, it is within the scope disclosed in the embodiments of the present specification. Specifically, the mass described in the embodiments of the present specification can be μg, mg, g, kg and other mass units known in the chemical industry.

[0052] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0053] In a first aspect, an embodiment of the present application provides a dispersant, including the following raw material components in parts by weight:

[0054] 25-50 parts of nonionic polymer, 25-60 parts of organic carboxylic acid, 5-20 parts of polyhydroxy aldehyde.

[0055] The dispersant provided in the first aspect of the embodiment of the present application has a certain complex adsorption effect between the functional groups of each component. Among them, the non-ionic polymer has no charged group and is non-ionic, and can better adjust the viscosity of the slurry in the dispersant. On the one hand, the terminal carboxyl group of the organic carboxylic acid can undergo complex adsorption with non-ionic polymers such as hydroxyl, lactam, amine, etc., forming an effective steric hindrance. On the other hand, the organic carboxylic acid can interact with some unique functional groups on the surface of the electrode active material to effectively reduce the surface tension of the solid-liquid interface. The functional groups on the polyhydroxy aldehyde are similar to those on the surface of the electrode active material, which play an electrostatic repulsion role and play a synergistic dispersion role with the organic carboxylic acid. Therefore, the dispersant formula can effectively promote the decrease of slurry viscosity, inhibit slurry gelation, increase the solid content of the battery pole piece, and thus improve the battery performance. Among them, if the content of the non-ionic polymer is too low, it is not conducive to providing sufficient steric hindrance, and if the content is too high, the slurry viscosity will rise due to its huge molecular weight. If the content of organic carboxylic acid is too low, the anchoring connection with the surface of the electrode active material is weak, which is not conducive to viscosity reduction. If the content is too high, the electrode slurry may be unstable and stratification may occur. If the content of polyhydroxy aldehyde is too high, it is not conducive to reducing the viscosity of the electrode slurry. If the content is too low, it is not enough to provide functional groups similar to those of the electrode active material. The components in the dispersant of the embodiment of the present application have surface functional groups that are the same or similar to the electrode active material, which can prevent the coating layer on the surface of the electrode active material from being damaged by excessive reaction. In addition, the components contained in the dispersant and their synergy play a great role in improving the dispersibility of the electrode slurry and reducing the viscosity of the slurry. Therefore, the dispersant of the embodiment of the present application can simultaneously play the role of improving the solid content of the electrode slurry, improving the fluidity of the electrode slurry, and preventing excessive dispersion from damaging the coating layer on the surface of the electrode active material.

[0056] The dispersant in the embodiment of the present application is particularly suitable for electrode slurry. The dispersant can be added in proportion during the electrode slurry slurry making process without adding any additional process cost. It can significantly increase the solid content of the electrode slurry, reduce the risk of electrode slurry aggregation, inhibit the gelation of the electrode slurry, and improve the fluidity of the electrode slurry, thereby reducing the resistance of the electrode sheet, and increasing the battery capacity without affecting the conductive performance.

[0057] The raw material components in the dispersant of the embodiment of the present application are: 25 to 50 parts of non-ionic polymer, 25 to 60 parts of organic carboxylic acid, and 5 to 20 parts of polyhydroxy aldehyde. Solvent is added and mixed to form a positive electrode material dispersant composition.

[0058] In some possible implementations, the dispersant further includes at least one solvent selected from N-methylpyrrolidone and N,N-dimethylformamide. These solvents have good solvent dispersion effects on components such as non-ionic polymers, polyhydroxy carboxylic acids, long-chain carboxylic acids, and polyhydroxy aldehydes.

[0059] In some possible implementations, the dispersant further includes a solvent having a mass percentage of 70% to 95%. In this case, the content of the solvent fully ensures the uniformity of dissolution and dispersion of each component in the dispersant, and is more conducive to adjusting the slurry viscosity, solid content and other properties. Exemplarily, in the dispersant, the mass percentage of the solvent is 70%, 80%, 90%, 95%, etc., which are typical but non-restrictive arbitrary point values ​​or interval values ​​between any two point values.

[0060] In some possible implementations, organic carboxylic acids include polyhydroxy carboxylic acids and long-chain carboxylic acids. The organic carboxylic acids in the embodiments of the present application include polyhydroxy carboxylic acids and long-chain carboxylic acids, wherein the long chain of the long-chain carboxyl group can provide a certain steric hindrance, which plays a role in improving the bonding stability of the dispersant. The hydroxyl groups, carboxyl groups and hydroxyl groups on the polyhydroxy carboxylic acids and polyhydroxy aldehydes are similar to the surface functional groups of the electrode active substances, which can play an electrostatic repulsion role to enhance the viscosity reduction effect. And it can form hydrogen bonds with the surface groups of the electrode active substances such as carbonyl, carboxyl, hydroxyl, etc., which plays a role in stabilizing the dispersion slurry. The carboxyl group in the organic carboxylic acid, on the one hand, can undergo complex adsorption with the hydroxyl group, lactam group, amine group, etc. in the non-ionic polymer to form an effective steric hindrance; on the other hand, the organic carboxylic acid can interact with some unique functional groups on the surface of the electrode active material, such as hydroxyl groups, to effectively reduce the surface tension of the solid-liquid interface.

[0061] In some possible implementations, the mass fraction of polyhydroxy carboxylic acid in the dispersant is 20 to 40 parts, and the mass fraction of long-chain carboxylic acid is 5 to 20 parts. In this case, if the content of long-chain carboxylic acid is too low, it is not conducive to providing sufficient steric hindrance. If the content is too high, the viscosity of the slurry will increase due to its huge molecular weight. If the content of polyhydroxy carboxylic acid is too low, it will not play an anchoring role and is not conducive to viscosity reduction. If the content is too high, it may cause the slurry to be unstable and stratification.

[0062] In some possible implementations, the dispersant includes the following raw material components in mass fractions: 25-50 parts of nonionic polymer, 20-40 parts of polyhydroxy carboxylic acid, 5-20 parts of long-chain carboxylic acid, and 5-20 parts of polyhydroxy aldehyde. The mass fraction of nonionic polymer can be 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, or any other typical but non-limiting values ​​or intervals between any two values; the mass fraction of polyhydroxy carboxylic acid can be 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, or any other typical but non-limiting values ​​or intervals between any two values; the mass fraction of long-chain carboxylic acid can be 5 parts, 10 parts, 15 parts, 20 parts, or any other typical but non-limiting values ​​or intervals between any two values; the mass fraction of polyhydroxy aldehyde can be 5 parts, 10 parts, 15 parts, 20 parts, or any other typical but non-limiting values ​​or intervals between any two values.

[0063] In some possible implementations, the nonionic polymer contains at least one functional group selected from the group consisting of hydroxyl, lactam, and amine. The nonionic polymer used in the embodiment of the present application has no charged groups and is non-ionic, and can better achieve the viscosity regulating effect in the dispersant. Avoid the problem that ionic polymers containing charged ionic groups are easy to flocculate in the dispersant. The nonionic polymer contains at least one functional group selected from the group consisting of hydroxyl, lactam, and amine, which can undergo complex adsorption with the terminal carboxyl group in the organic carboxylic acid to form an effective steric hindrance, reduce the surface tension of the solid-liquid interface, increase the solid content of the slurry, and reduce the risk of slurry aggregation.

[0064] In some possible implementations, the weight average molecular weight of the nonionic polymer is 10,000 to 50,000. In this case, the nonionic polymer can better adjust the viscosity of the slurry. Exemplarily, the weight average molecular weight of the nonionic polymer can be 10,000, 20,000, 30,000, 40,000, 50,000, etc., which are typical but non-limiting values, or an interval value between any two values.

[0065] In some possible implementations, the nonionic polymer includes a structure wait.

[0066] In some possible implementations, the nonionic polymer includes at least one of methyl pyrrolidone, polyethylene glycol, polyvinyl alcohol, and polyacrylamide; these nonionic polymers can effectively adjust the viscosity of the slurry. In addition, the functional groups such as hydroxyl, lactam, and amine in the nonionic polymer can undergo complex adsorption with the terminal carboxyl groups in the organic carboxylic acid to form an effective steric hindrance, reduce the surface tension of the solid-liquid interface, increase the solid content of the slurry, and reduce the risk of slurry aggregation.

[0067] In some possible implementations, the number of hydroxyl groups in the polyhydroxy aldehyde is at least 2; in this case, a sufficient number of hydroxyl groups can play an important anchoring role. The more hydroxyl groups in the polyhydroxy aldehyde, the stronger the activity, and the more roles it plays in the dispersant. The functional groups such as hydroxyl groups and aldehyde groups are similar to the functional groups on the surface of the electrode active material, which can not only play an electrostatic repulsion role to enhance the viscosity reduction effect, but also can form hydrogen bonds with the surface groups of the electrode active material to stabilize the dispersion slurry.

[0068] In some possible implementations, the weight average molecular weight of the polyhydroxy aldehyde is 180 to 360. The higher the weight average molecular weight of the polyhydroxy aldehyde, the less conducive it is to reducing the viscosity of the slurry. In this case, the polyhydroxy aldehyde can better adjust the viscosity of the slurry and better stabilize the dispersed slurry. Exemplarily, the weight average molecular weight of the polyhydroxy aldehyde can be 180, 200, 250, 300, 350, 360, etc., typical but non-limiting arbitrary point values ​​or interval values ​​between any two point values.

[0069] In some possible implementations, the polyhydroxy aldehyde comprises the structure wait.

[0070] In some possible implementations, the polyhydroxy aldehyde includes at least one of glucose, fructose, and glyceraldehyde; these polyhydroxy aldehydes have groups similar to the functional groups on the surface of the electrode active material, which can play an electrostatic repulsion role to achieve a viscosity reduction effect, and can form hydrogen bonds with the surface groups of the electrode active material to better stabilize the dispersed slurry.

[0071] In some possible implementations, the number of hydroxyl groups in the polyhydroxycarboxylic acid is at least 2. In this case, the number of hydroxyl groups in the polyhydroxycarboxylic acid is 2 or more, and the number of carboxyl groups is 1 or more. A sufficient number of hydroxyl groups on the polyhydroxycarboxylic acid can play an important anchoring role. The more hydroxyl groups there are, the stronger the activity is, and the more roles they play in the dispersant, such as deprotonation to form a more stable ring structure, and they can form better hydrogen bonds with the surface groups of the active substances, which is beneficial to the slurry stability and viscosity reduction.

[0072] In some possible implementations, the weight average molecular weight of the polyhydroxycarboxylic acid is 150 to 1800. In this case, the molecular weight of the polyhydroxycarboxylic acid within 2000 can better reduce the slurry viscosity and improve the slurry stability. If the weight average molecular weight of the polyhydroxycarboxylic acid is too high, its effect on reducing the slurry viscosity will be reduced. In some embodiments, the weight average molecular weight of the polyhydroxycarboxylic acid can be 150, 200, 300, 500, 800, 1000, 1300, 1500, 1800, 2000, etc., typical but non-limiting arbitrary point values ​​or interval values ​​between any two point values.

[0073] In some possible implementations, the polyhydroxycarboxylic acid comprises the structural formula: wait.

[0074] In some possible implementations, the polyhydroxycarboxylic acid includes at least one of citric acid, tartaric acid, phytic acid, and gallic acid. These polyhydroxycarboxylic acids can electrostatically repel the electrode active material to enhance the viscosity reduction effect; and they can form hydrogen bonds with the surface groups of the electrode active material to stabilize the dispersed slurry.

[0075] In some possible implementations, the number of carbon atoms in the carbon chain of the long-chain carboxylic acid is not less than 12. In this case, only a sufficient carbon chain length can play a steric hindrance role. The carbon chain length in the long-chain carboxylic acid is twelve or more, and the carbon chain is long enough to play a better steric hindrance role. It can undergo complex adsorption with hydroxyl groups, lactam groups, amine groups, etc. in non-ionic polymers to form a more effective steric hindrance, and can cooperate well with polyhydroxy aldehydes to reduce viscosity, reduce the surface tension of the solid-liquid interface, and increase the solid content of the slurry. In some embodiments, the number of carbon atoms in the carbon chain of the long-chain carboxylic acid is 12 to 20, and can specifically be 12, 13, 14, 15, 16, 17, 18, 19, 20, etc., typical but non-restrictive arbitrary point values ​​or interval values ​​between any two point values, which can cooperate well with polyhydroxy aldehydes to reduce viscosity.

[0076] In some possible implementations, the weight average molecular weight of the long-chain carboxylic acid is 200 to 300. In this case, the weight average molecular weight of the long-chain carboxylic acid is 200 and above. The higher the molecular weight, the better the steric hindrance, which is more conducive to reducing the surface tension of the solid-liquid interface and increasing the solid content of the slurry. In some embodiments, the weight average molecular weight of the long-chain carboxylic acid is 200, 220, 240, 250, 260, 280, 300, etc., typical but non-limiting arbitrary point values ​​or interval values ​​between any two point values.

[0077] In some possible implementations, the long-chain carboxylic acid comprises a structural formula comprising wait.

[0078] In some possible implementations, the long-chain carboxylic acid includes at least one of palmitic acid, stearic acid, and fatty acids; these long-chain carboxylic acids can undergo complex adsorption with hydroxyl groups, lactam groups, amine groups, etc. in non-ionic polymers to form more effective steric hindrance, reduce the surface tension of the solid-liquid interface, and increase the solid content of the slurry.

[0079] The dispersant of the present application can be prepared by the following method.

[0080] In a second aspect, the present invention provides a method for preparing a dispersant, as shown in the attached Figure 1 As shown, the following steps are included:

[0081] S10. Mix 25 to 50 parts of a nonionic polymer, 25 to 60 parts of an organic carboxylic acid, and 5 to 20 parts of a polyhydroxy aldehyde with a solvent to prepare a dispersant.

[0082] The preparation method of the dispersant of the embodiment of the present application is to fully dissolve and disperse 25 to 50 parts of non-ionic polymer, 25 to 60 parts of organic carboxylic acid, and 5 to 20 parts of polyhydroxy aldehyde in a solvent, and observe that the solution is in a clear state to obtain a dispersant. The preparation process is simple and suitable for industrial large-scale production and application. There is a certain complexation adsorption effect between the functional groups of each component in the prepared dispersant. Among them, the non-ionic polymer has no charged group and is non-ionic, and can better adjust the viscosity of the slurry in the dispersant. The amount of non-ionic polymer fully ensures that it forms an effective steric hindrance with organic carboxylic acid through complexation adsorption, thereby increasing the solid content of the slurry. The amount of organic carboxylic acid and polyhydroxy aldehyde not only ensures that the slurry has a suitable viscosity, but also can effectively improve the dispersion stability, fluidity and other characteristics of the slurry; and the functional groups in organic carboxylic acid and polyhydroxy aldehyde are similar to the groups on the surface of the electrode active material in the electrode slurry, which is beneficial to prevent the coating layer on the surface of the electrode active material from being destroyed by excessive reaction. Through the joint action of various components in the dispersant, the solid content of the electrode slurry can be increased, the fluidity of the electrode slurry can be improved, and excessive dispersion can be prevented from destroying the surface coating layer of the electrode active material.

[0083] In some possible implementations, the organic carboxylic acid includes 20 to 40 parts of polyhydroxy carboxylic acid and 5 to 20 parts of long-chain carboxylic acid. Among them, the hydroxyl group and carboxyl group in the polyhydroxy carboxylic acid are similar to the surface functional groups of the electrode active material, which can play an electrostatic repulsion role to enhance the viscosity reduction effect; and it can form hydrogen bonds with the surface groups of the electrode active material such as carbonyl, carboxyl, hydroxyl, etc., to stabilize the dispersion slurry. The carboxyl group in the organic carboxylic acid can not only undergo complex adsorption with the hydroxyl group, lactam group, amine group, etc. in the non-ionic polymer to form an effective steric hindrance; it can also interact with some unique functional groups on the surface of the electrode active material, such as hydroxyl, to effectively reduce the surface tension of the solid-liquid interface. If the content of the long-chain carboxylic acid is too low, it is not conducive to providing sufficient steric hindrance. If the content is too high, the viscosity of the slurry will increase due to its huge molecular weight. If the content of the polyhydroxy carboxylic acid is too low, it will not play an anchoring role, which is not conducive to viscosity reduction. If the content is too high, the slurry may be unstable and stratification may occur.

[0084] In some possible implementations, the mass percentage of the solvent in the dispersant is 70% to 95%. In this case, the content of the solvent fully ensures the uniformity of dissolution and dispersion of each component in the dispersant, and is more conducive to adjusting the slurry viscosity, solid content and other properties.

[0085] In some possible implementations, the nonionic polymer includes at least one of methyl pyrrolidone, polyethylene glycol, polyvinyl alcohol, and polyacrylamide; these nonionic polymers can effectively adjust the viscosity of the slurry. In addition, the functional groups such as hydroxyl, lactam, and amine in the nonionic polymer can undergo complex adsorption with the terminal carboxyl groups in the organic carboxylic acid to form an effective steric hindrance, reduce the surface tension of the solid-liquid interface, increase the solid content of the slurry, and reduce the risk of slurry aggregation.

[0086] In some possible implementations, the organic carboxylic acids include at least one polyhydroxy carboxylic acid selected from citric acid, tartaric acid, phytic acid, and gallic acid; these polyhydroxy carboxylic acids can electrostatically repel each other with the electrode active substance to enhance the viscosity reduction effect; and they can form hydrogen bonds with the surface groups of the electrode active substance to stabilize the dispersed slurry.

[0087] In some possible implementations, the organic carboxylic acids include at least one long-chain carboxylic acid selected from palmitic acid, stearic acid, and fatty acids; these long-chain carboxylic acids can undergo complex adsorption with hydroxyl groups, lactam groups, amine groups, etc. in non-ionic polymers to form more effective steric hindrance, reduce the surface tension of the solid-liquid interface, and increase the solid content of the slurry.

[0088] In some possible implementations, the polyhydroxy aldehyde includes at least one of glucose, fructose, and glyceraldehyde; these polyhydroxy aldehydes have groups similar to the functional groups on the surface of the electrode active material, which can play an electrostatic repulsion role to achieve a viscosity reduction effect, and can form hydrogen bonds with the surface groups of the electrode active material to better stabilize the dispersed slurry.

[0089] In some possible implementations, the solvent includes at least one of N-methylpyrrolidone and N,N-dimethylformamide. These solvents have good solvent dispersion effects on components such as non-ionic polymers, polyhydroxy carboxylic acids, long-chain carboxylic acids, and polyhydroxy aldehydes.

[0090] In some possible implementations, the mixing process includes the steps of: mixing the nonionic polymer and the solvent, stirring for 3 to 6 hours under the condition of an oil bath temperature of 30°C to 60°C and a rotation speed of 300 rpm to 1200 rpm until they are completely dissolved to obtain a clear solution; and adding an organic carboxylic acid and a polyhydroxy aldehyde respectively and stirring for 3 to 6 hours to obtain the clear dispersant. Under such mixing conditions, it is possible to fully ensure that a uniformly dispersed and stable dispersant solution is obtained.

[0091] In a third aspect, an embodiment of the present application provides a secondary battery, comprising an electrode sheet and an electrolyte; wherein the electrode slurry for preparing the electrode sheet comprises an electrode active material, a conductive agent, a binder, a solvent and the above-mentioned dispersant and / or the dispersant prepared by the above-mentioned method.

[0092] In the secondary battery of the embodiment of the present application, the above dispersant is added to the electrode slurry for preparing the electrode sheet. The dispersant can simultaneously increase the solid content of the electrode slurry and improve the fluidity of the electrode slurry through the joint action of various components, and prevent excessive dispersion from damaging the surface coating layer of the electrode active material. Therefore, it is beneficial to improve the uniformity, stability, content of electrode active materials and other properties of the electrode sheet, thereby improving the electrochemical properties of the secondary battery such as gram capacity, stability, and cycle life.

[0093] In some possible implementations, the mass percentage of the dispersant in the electrode slurry is 0.1% to 0.5%. Under this content, the dispersibility and uniformity of the electrode material can be fully improved to avoid particle accumulation and agglomeration, and the solid content of the electrode slurry can be increased, avoiding the influence of the dispersant on the electrochemical performance and stability of the electrode material, and will not reduce the gram capacity of the electrode sheet, thereby ensuring its electrochemical performance.

[0094] In some possible implementations, the electrode sheet may be a positive electrode sheet or a negative electrode sheet, including a current collector and an electrode active layer formed on the surface of the current collector, wherein the electrode active layer includes an electrode active material, a conductive agent, a binder and the above-mentioned dispersant. The uniformity, gram capacity, stability, cycle life and other characteristics of the electrode active layer in the electrode sheet are improved.

[0095] In some possible implementations, in the electrode sheet, the surface of the electrode active material has a carbon coating layer grafted with at least one of carbonyl, ether, and phenolic hydroxyl groups. In this case, on the one hand, the carbon coating layer can improve the conductivity, stability and other properties of the electrode active material, and on the other hand, the carbonyl, ether, phenolic hydroxyl and other groups grafted on these carbon coating layers have a better coordination effect with the functional groups of the components in the dispersant, and through electrostatic repulsion, hydrogen bonding, etc., it can not only better improve the viscosity reduction effect on the electrode slurry, but also better protect the surface coating layer of the electrode active material from being damaged by excessive reaction.

[0096] In some possible implementations, the electrode sheet is a positive electrode sheet including a current collector and a positive electrode active layer formed on a surface of the current collector, wherein the positive electrode active layer contains a positive electrode active material, a conductive agent, a binder and the above-mentioned dispersant.

[0097] In some embodiments, the positive electrode active material includes lithium iron phosphate synthesized by a solid phase method. In this case, the surface of the lithium iron phosphate synthesized by a solid phase method has a carbon coating layer, and groups such as carbonyl, ether, and phenolic hydroxyl groups are grafted onto the carbon coating layer.

[0098] In some possible implementations, the preparation of the positive electrode active layer includes the steps of: mixing the positive electrode active material, the conductive agent, the binder and the dispersant to form an electrode slurry, coating the electrode slurry on the current collector, and preparing the positive electrode sheet through the steps of drying, rolling, die cutting, etc. In some embodiments, after the prepared dispersant is diluted to a certain concentration, it is added to the electrode slurry as needed, or the dispersant is directly added to the electrode slurry according to a calculated amount.

[0099] In some possible implementations, the mass percentage of the positive active material in the positive active layer of the positive electrode sheet is 90% to 95%. Specifically, the mass percentage of the positive active material in the positive active material layer can be 90%, 91%, 92%, 93%, 94%, 95%, etc.

[0100] In some possible implementations, the current collector of the positive electrode sheet includes but is not limited to any one of copper foil and aluminum foil.

[0101] In some possible implementations, the content of the binder in the active material layer of the positive electrode sheet is 2 wt% to 5 wt%. In specific embodiments, the content of the binder can be 2 wt%, 3 wt%, 4 wt%, 5 wt%, etc., which are typical but not limiting contents.

[0102] In some possible implementations, the binder includes one or more of polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan, and chitosan derivatives.

[0103] In some possible implementations, the content of the conductive agent in the active material layer of the positive electrode sheet is 1 wt% to 5 wt%. In specific embodiments, the content of the conductive agent can be 3 wt%, 4 wt%, 5 wt%, etc., which are typical but not limiting contents.

[0104] In some possible implementations, the conductive agent includes one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60, and carbon nanotubes.

[0105] In some possible implementations, the electrode sheet is a negative electrode sheet, including a current collector and a negative electrode active layer formed on the surface of the current collector, wherein the negative electrode active layer contains a negative electrode active material, a conductive agent, a binder and the above-mentioned dispersant.

[0106] In some possible embodiments, the steps of making a negative electrode sheet include: mixing a negative electrode active material with a conductive agent such as conductive carbon black, a binder such as carboxymethyl cellulose and styrene-butadiene rubber, a dispersant and a solvent such as water in a mass ratio of (80-99):(1-5):(2-10):100 to make a negative electrode mixed slurry, vacuum degassing, discharging, coating on a coating machine, and obtaining a negative electrode sheet after rolling, slitting and die-cutting.

[0107] In some possible implementations, the negative electrode active material includes but is not limited to carbon materials such as graphite, soft carbon (such as coke), hard carbon, or nitrides, tin-based oxides, tin-based oxides, tin alloys, and nano-negative electrode materials.

[0108] In some possible implementations, the negative electrode current collector includes but is not limited to any one of copper foil and aluminum foil.

[0109] In some possible implementations, the electrolyte may be a liquid electrolyte or a solid electrolyte. When a liquid electrolyte is selected, the secondary battery further includes a separator.

[0110] In some possible implementations, the secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte, etc., wherein the positive electrode sheet and / or the negative electrode sheet contains the above-mentioned dispersant.

[0111] In some possible implementations, the separator can block the passage of electrons and allow the passage of ions. Exemplarily, the separator includes, but is not limited to, at least one material selected from polypropylene fiber, polyacrylonitrile fiber, polyvinyl formal fiber, poly(ethylene terephthalate), polyethylene terephthalate, polyamide fiber, and poly(p-phenylene terephthalamide).

[0112] In some possible implementations, the electrolyte includes at least one soluble metal salt. In some specific embodiments, the metal salt includes LiClO 4 , LiBF 4 、LiPF 6 、LiAsF 6 、LiCF 3 SO 3 、LiTDI、Li[(CF 3 SO 2 ) 2 N]、Li[(FSO 2 ) 2 N]、Li[(C m F 2m+1 SO 2 )(C n F 2n+1 SO 2)N], wherein m and n are natural numbers. These electrolytic salts can ensure high ionic conductivity of the electrolyte, and do not cause harmful side reactions with electrode materials, electrolytes, diaphragms, etc., and have good chemical stability.

[0113] In some possible implementations, the secondary battery includes at least one of a battery cell, a battery module, and a battery pack.

[0114] In some possible implementations, the battery cell types include lithium-ion batteries, as well as new batteries such as lithium-air batteries and lithium metal batteries.

[0115] In some possible implementations, the battery cells of the present application can be assembled into a battery module, and the number of battery cells contained in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module. Further, the battery module can also include a housing with a storage space, and multiple battery cells are stored in the storage space.

[0116] In a possible implementation, the battery cells and / or battery modules may also be assembled into a battery pack, and the number of battery cells or battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0117] In order to enable the above implementation details and operations of the present application to be clearly understood by those skilled in the art, and to demonstrate the significant improvement in the performance of the dispersant and preparation method thereof in the embodiments of the present application, the above technical solution is illustrated by means of multiple embodiments below.

[0118] Example 1

[0119] A dispersant, the preparation of which comprises the following steps: using N-methylpyrrolidone as a solvent, putting 45 parts of polyvinylpyrrolidone (K30) into a stirring tank, stirring at a speed of 500 rpm for 1 hour at room temperature until completely dissolved, then adding 35 parts of phytic acid and 12 parts of palmitic acid respectively, after dissolving for 2 hours, adding 8 parts of glucose and stirring for 2 hours to obtain a clear dispersant solution.

[0120] Example 2

[0121] A dispersant, the preparation of which comprises the steps of: using N-methylpyrrolidone as a solvent, putting 25 parts of polyvinylpyrrolidone (K30) into a stirring tank, stirring at a speed of 500 rpm for 1 hour at room temperature until completely dissolved, then adding 40 parts of phytic acid and 20 parts of palmitic acid respectively, dissolving for 2 hours, then adding 15 parts of glucose and stirring for 2 hours to obtain a clear dispersant solution.

[0122] Example 3

[0123] A dispersant, the preparation of which comprises the following steps: using N-methylpyrrolidone as a solvent, putting 50 parts of polyvinylpyrrolidone (K30) into a stirring tank, stirring at a speed of 500 rpm for 1 hour at room temperature until completely dissolved, then adding 32 parts of phytic acid and 11 parts of palmitic acid respectively, and after dissolving for 2 hours, adding 7 parts of glucose and stirring for 2 hours to obtain a clear dispersant solution.

[0124] Example 4

[0125] A dispersant, the preparation of which comprises the following steps: using N-methylpyrrolidone as a solvent, putting 45 parts of polyvinylpyrrolidone (K30) into a stirring tank, stirring at a speed of 500 rpm for 1 hour at room temperature until completely dissolved, then adding 20 parts of phytic acid and 20 parts of palmitic acid respectively, after dissolving for 2 hours, adding 15 parts of glucose and stirring for 2 hours to obtain a clear dispersant solution.

[0126] Example 5

[0127] A dispersant, the preparation of which comprises the following steps: using N-methylpyrrolidone as a solvent, putting 45 parts of polyvinylpyrrolidone (K30) into a stirring tank, stirring at a speed of 500 rpm for 1 hour at room temperature until completely dissolved, then adding 40 parts of phytic acid and 5 parts of palmitic acid respectively, dissolving for 2 hours, then adding 10 parts of glucose and stirring for 2 hours to obtain a clear dispersant solution.

[0128] Example 6

[0129] A dispersant, the preparation of which comprises the following steps: using N-methylpyrrolidone as a solvent, putting 40 parts of polyvinylpyrrolidone (K30) into a stirring tank, stirring at a speed of 500 rpm for 1 hour at room temperature until completely dissolved, then adding 31 parts of phytic acid and 9 parts of palmitic acid respectively, dissolving for 2 hours, then adding 20 parts of glucose and stirring for 2 hours to obtain a clear dispersant solution.

[0130] Example 7

[0131] A dispersant, the preparation of which comprises the following steps: using N-methylpyrrolidone as a solvent, putting 46 parts of polyvinylpyrrolidone (K30) into a stirring tank, stirring at a speed of 500 rpm for 1 hour at room temperature until completely dissolved, then adding 36 parts of phytic acid and 13 parts of palmitic acid respectively, dissolving for 2 hours, then adding 5 parts of glucose and stirring for 2 hours to obtain a clear dispersant solution.

[0132] Example 8

[0133] A dispersant, the preparation of which comprises the following steps: using N-methylpyrrolidone as a solvent, putting 38.5 parts of polyvinylpyrrolidone (K30) into a stirring tank, stirring at a speed of 500 rpm for 1 hour at room temperature until completely dissolved, then adding 30.5 parts of phytic acid and 15.5 parts of palmitic acid respectively, after dissolving for 2 hours, adding 15.5 parts of glucose and stirring for 2 hours to obtain a clear dispersant solution.

[0134] Comparative Example 1

[0135] A dispersant, the preparation of which comprises the following steps: using N-methylpyrrolidone as a solvent, putting 45 parts of ionic polyacrylamide into a stirring tank, stirring at a speed of 500 rpm for 1 hour at room temperature until completely dissolved, then adding 35 parts of phytic acid and 12 parts of palmitic acid respectively, dissolving for 2 hours, then adding 8 parts of glucose and stirring for 2 hours to obtain a clear dispersant solution.

[0136] Comparative Example 2

[0137] A dispersant, the preparation of which comprises the following steps: using N-methylpyrrolidone as a solvent, putting 45 parts of polyvinylpyrrolidone (K30) into a stirring tank, stirring at a speed of 500 rpm for 1 hour at room temperature until completely dissolved, then adding 35 parts of phytic acid and 12 parts of n-butyric acid respectively, and after dissolving for 2 hours, adding 8 parts of glucose and stirring for 2 hours to obtain a clear dispersant solution.

[0138] Comparative Example 3

[0139] A dispersant, the preparation of which comprises the following steps: using N-methylpyrrolidone as a solvent, putting 45 parts of polyvinylpyrrolidone (K30) into a stirring tank, stirring at a speed of 500 rpm for 1 hour at room temperature until completely dissolved, then adding 35 parts of cinnamic acid and 12 parts of palmitic acid respectively, after dissolving for 2 hours, adding 8 parts of glucose and stirring for 2 hours to obtain a clear dispersant solution.

[0140] Comparative Example 4

[0141] A dispersant, the preparation of which comprises the following steps: using N-methylpyrrolidone as a solvent, putting 70 parts of polyvinylpyrrolidone (K30) into a stirring tank, stirring at a speed of 500 rpm for 1 hour at room temperature until completely dissolved, then adding 20 parts of phytic acid and 5 parts of palmitic acid respectively, after dissolving for 2 hours, adding 5 parts of glucose and stirring for 2 hours to obtain a clear dispersant solution.

[0142] Comparative Example 5

[0143] A dispersant, the preparation of which comprises the following steps: using N-methylpyrrolidone as a solvent, putting 25 parts of polyvinylpyrrolidone (K30) into a stirring tank, stirring at a speed of 500 rpm for 1 hour at room temperature until completely dissolved, then adding 65 parts of phytic acid and 5 parts of palmitic acid respectively, after dissolving for 2 hours, adding 5 parts of glucose and stirring for 2 hours to obtain a clear dispersant solution.

[0144] Comparative Example 6

[0145] A dispersant, the preparation of which comprises the following steps: using N-methylpyrrolidone as a solvent, putting 45 parts of polyvinylpyrrolidone (K30) into a stirring tank, stirring at a speed of 500 rpm for 1 hour at room temperature until completely dissolved, then adding 40 parts of phytic acid and 0 parts of palmitic acid respectively, and after dissolving for 2 hours, adding 15 parts of glucose and stirring for 2 hours to obtain a clear dispersant solution.

[0146] Comparative Example 7

[0147] A dispersant, the preparation of which comprises the following steps: using N-methylpyrrolidone as a solvent, putting 40 parts of polyvinylpyrrolidone (K30) into a stirring tank, stirring at a speed of 500 rpm for 1 hour at room temperature until completely dissolved, then adding 25 parts of phytic acid and 5 parts of palmitic acid respectively, dissolving for 2 hours, then adding 30 parts of glucose and stirring for 2 hours to obtain a clear dispersant solution.

[0148] Comparative Example 8

[0149] A dispersant, the preparation of which comprises the following steps: using N-methylpyrrolidone as a solvent, putting 45 parts of polyvinylpyrrolidone (K15) into a stirring tank, stirring at a speed of 500 rpm for 1 hour at room temperature until completely dissolved, then adding 35 parts of phytic acid and 12 parts of palmitic acid respectively, after dissolving for 2 hours, adding 8 parts of glucose and stirring for 2 hours to obtain a clear dispersant solution.

[0150] The dispersant components and ratios, polymer molecular weight, dispersant viscosity and other parameters provided in the above embodiments and comparative examples are shown in Table 1 below:

[0151] Table 1

[0152]

[0153]

[0154] It can be seen from the test results in Table 1 above that the viscosity of the dispersants provided in Examples 1 to 8 of the present application is mainly between 160 mPa·s and 200 mPa·s, which is a relatively moderate viscosity range.

[0155] In order to verify the progress of the embodiments of the present application, the following performance tests were performed on the above embodiments and comparative examples respectively:

[0156] The dispersants provided in the above Examples 1-8 and the dispersants provided in Comparative Examples 1-8 were respectively prepared into positive electrode slurries according to the following methods:

[0157] The dispersant was added to the positive electrode slurry of lithium iron phosphate (LFP) battery and named as Verification Example B1-Verification Example B8, Comparative Verification Example B1-Comparative Verification Example B8. Among them, the positive electrode slurry of lithium iron phosphate battery is mixed with solid dry material and N-methylpyrrolidone (wherein, the weight of N-methylpyrrolidone is 41.75wt% of the total weight of the positive electrode slurry). Based on the total weight of 100wt%, the solid dry material in the positive electrode slurry includes 96.5wt% of lithium iron phosphate, 1.3wt% of Super P and 2.2wt% of polyvinylidene fluoride. Polyvinylidene fluoride and Super P were stirred at 400 rpm in N-methylpyrrolidone for 20 minutes, lithium iron phosphate was added and stirred at 200 rpm for 10 minutes, and then the dispersant was added and stirred at 2000 rpm for 70 minutes to obtain the positive electrode slurry.

[0158] The above-mentioned verification examples B1 to B8 and comparative verification examples B1 to B8 were tested as follows, and the test results shown in Table 2 below were obtained:

[0159] 1. Viscosity test: Verification Example B1-Verification Example B8, Comparative Verification Example B1-Comparative Verification Example B8, test the viscosity of the slurry at the time of discharge and 24h respectively. Select a suitable rotor, fix the viscometer rotor, place the glue under the viscometer rotor, and the glue just submerges the scale line of the rotor. Instrument model: Shanghai Fangrui NDJ-5S, rotor: 64#, speed: 15-30r / min, test temperature: 25℃, test humidity: 20RH%~30RH%, test time is 1min, and read the data after the display is stable. The viscosity reference value of the original positive electrode slurry (without adding dispersant) is (10000±2000)mPa·s.

[0160] 2. Fluidity test: For the slurry fluidity test, take an appropriate amount of positive electrode slurry with a medicine spoon (Verification Example B1-Verification Example B8, Comparative Verification Example B1-Comparative Verification Example B8), and observe whether the positive electrode slurry flows smoothly. If the natural flow is smooth, it is judged as OK; if the fluidity is not good, the slurry appears jelly-like and lumpy, indicating the presence of gel, it is judged as NG. Among them, DY-12, DY-17, YN-7, and S20 are all LFP models available on the market. For example, the DY series is purchased from Defang Nano. Differences in the slurry environment of the LFP models used:

[0161] DY-12, DY-17: The positive electrode active material focuses on neutralizing residual alkali. The use of dispersant is to improve the fluidity of the slurry and maintain the stability of the surface coating layer;

[0162] YN-7, S20: The use of dispersants is to ensure uniform dispersion, increase the solid content of the slurry and not damage the surface coating.

[0163] The above test results are shown in Table 2 below:

[0164] Table 2

[0165]

[0166]

[0167]

[0168] It can be seen from the test results in Table 2 above that after the dispersants provided in Examples 1 to 8 of the present application and Comparative Examples 1 to 8 are applied to the positive electrode slurry under the same conditions, the positive electrode slurry added with the dispersants in Examples 1 to 8 of the present application exhibits a higher solid content, better slurry fluidity and stability, and the viscosity increase of the positive electrode slurry after 24 hours of placement is much lower than that of the slurry added with the dispersants in the comparative examples. In addition, the actual flow pictures of the discharge of the positive electrode slurry provided in Verification Examples B1 and B4 and Verification Comparative Examples B1 and B8 are shown in the attached figure. Figure 2 As shown, it can be seen that the positive electrode slurries of verification examples B1 and B4 of the present application exhibit better fluidity.

[0169] From the above description, the components contained in the dispersant of the embodiment of the present application play a great role in improving the dispersibility of the electrode slurry and adjusting the viscosity of the slurry. It can also play a role in increasing the solid content of the electrode slurry, improving the fluidity of the electrode slurry and preventing excessive dispersion from damaging the surface coating layer of the electrode active material.

[0170] The positive electrode slurry (DY-12) provided in the above Verification Examples B1-B8 and Comparative Verification Examples B1-B8 was coated on the current collector to make a positive electrode sheet, and the positive electrode sheet was assembled into a secondary battery, and the electrochemical performance of the secondary battery was tested. In addition, the cycle capacity measurement was recorded from the second cycle after the first charge and discharge, that is, the cycle started from the second cycle after the first charge and discharge. The test results are shown in Table 3 and Attached Figures 3 to 6 As shown:

[0171] Table 3

[0172]

[0173]

[0174] From the test results in Table 3 above, it can be seen that after the positive electrode slurry (DY-12) provided by Verification Examples B1-B8 and Comparative Verification Examples B1-B8 of this application is applied to the secondary battery under the same conditions, the secondary battery applied by Verification Examples B1-B8 of this application shows better charge and discharge capacity in the first three cycles of 0.1C, and shows higher capacity retention rate after 400 cycles at 1C rate capacity. In addition, from the attached Figures 3 to 6 The charge and discharge curves of the batteries of the verification examples B1 and B4 and the verification comparative examples B1 and B8 show that the batteries corresponding to the verification examples B1 and B4 of the present application show better cycle stability. Therefore, the dispersant of the present application improves the electrochemical properties of the secondary battery, such as capacity, stability and cycle life.

[0175] In addition, it should be noted that the positive electrode slurry has good fluidity within a few hours after discharge. The positive electrode slurry will be coated on the current collector at this time to ensure the coating effect. The coating will generally not be applied until 24 hours later. The main factor affecting the battery's electrical performance is the inherent redox characteristics of the dispersant itself. Therefore, when the material and content in the dispersant fluctuate slightly, the electrochemical performance will deteriorate slightly, but there will not be a huge change.

[0176] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A dispersant, characterized in that: The raw material components include the following parts by weight: 25-50 parts of nonionic polymer, 25-60 parts of organic carboxylic acid, 5-20 parts of polyhydroxy aldehyde.

2. The dispersant according to claim 1, characterized in that The organic carboxylic acids include polyhydroxy carboxylic acids and long-chain carboxylic acids.

3. The dispersant according to claim 2, characterized in that In the dispersant, the mass fraction of the polyhydroxy carboxylic acid is 20 to 40 parts, and the mass fraction of the long-chain carboxylic acid is 5 to 20 parts.

4. The dispersant according to claim 3, characterized in that The number of hydroxyl groups in the polyhydroxy aldehyde is at least 2; and / or, the number of hydroxyl groups in the polyhydroxy carboxylic acid is at least 2; and / or, the number of carbon atoms in the carbon chain of the long-chain carboxylic acid is not less than 12; And / or, the nonionic polymer contains at least one functional group selected from the group consisting of a hydroxyl group, a lactam group, and an amine group.

5. The dispersant according to claim 3, characterized in that The weight average molecular weight of the nonionic polymer is 10,000 to 50,000; and / or, the weight average molecular weight of the long-chain carboxylic acid is 200 to 300; and / or, the weight average molecular weight of the polyhydroxycarboxylic acid is 150 to 1800; And / or, the weight average molecular weight of the polyhydroxy aldehyde is 180-360.

6. The dispersant according to any one of claims 2 to 5, characterized in that The nonionic polymer includes at least one of methyl pyrrolidone, polyethylene glycol, polyvinyl alcohol, and polyacrylamide; and / or, the polyhydroxycarboxylic acid comprises at least one of citric acid, tartaric acid, phytic acid, and gallic acid; And / or, the long-chain carboxylic acid comprises at least one of palmitic acid, stearic acid, and fatty acid; and / or, the polyhydroxy aldehyde comprises at least one of glucose, fructose, and glyceraldehyde; And / or, the dispersant further comprises at least one solvent selected from N-methylpyrrolidone and N,N-dimethylformamide; And / or, the dispersant further comprises a solvent in an amount of 70% to 95% by mass.

7. A method for preparing a dispersant, characterized in that: The following steps are involved: 25-50 parts of nonionic polymer, 25-60 parts of organic carboxylic acid, 5-20 parts of polyhydroxy aldehyde and solvent are mixed to prepare a dispersant.

8. The method for preparing a dispersant according to claim 7, characterized in that: The mixing process comprises the steps of: mixing the nonionic polymer and the solvent, stirring for 3 to 6 hours under the condition of an oil bath temperature of 30° C. to 60° C. and a rotation speed of 300 rpm to 1200 rpm to obtain a clear solution; respectively adding the organic carboxylic acid and the polyhydroxy aldehyde and stirring for 3 to 6 hours to obtain a clear dispersant; and / or, the organic carboxylic acid comprises 20 to 40 parts of polyhydroxy carboxylic acid and 5 to 20 parts of long-chain carboxylic acid; And / or, in the dispersant, the mass percentage of the solvent is 70% to 95%; And / or, the nonionic polymer includes at least one of methyl pyrrolidone, polyethylene glycol, polyvinyl alcohol, and polyacrylamide; and / or, the organic carboxylic acid comprises at least one polyhydroxy carboxylic acid selected from citric acid, tartaric acid, phytic acid and gallic acid; And / or, the organic carboxylic acid includes at least one long-chain carboxylic acid selected from palmitic acid, stearic acid and fatty acid; and / or, the polyhydroxy aldehyde comprises at least one of glucose, fructose, and glyceraldehyde; And / or, the solvent includes at least one of N-methylpyrrolidone and N,N-dimethylformamide.

9. A secondary battery, characterized in that: It comprises an electrode sheet and an electrolyte; wherein the electrode slurry for preparing the electrode sheet comprises an electrode active material, a conductive agent, a binder, a solvent and a dispersant as described in any one of claims 1 to 6 and / or a dispersant prepared by the method as described in any one of claims 7 to 8.

10. The secondary battery according to claim 9, characterized in that In the electrode slurry, the mass percentage of the dispersant is 0.1% to 0.5%; And / or, the electrode sheet is a positive electrode sheet, and the surface of the electrode active material has a carbon coating layer grafted with at least one group of carbonyl, ether, and phenolic hydroxyl.